The Violence of Work: New Essays in Canadian and US Labour History - Milloy, Jeremy; Sangster, Joan (2020)
From mining to sex work and from the classroom to the docks, violence has always been a part of work. This collection of essays highlights the many different forms and expressions of violence that have arisen under capitalism in the last two hundred years, as well as how historians of working-class life and labour have understood violence. The editors draw together diverse case studies, integrating analysis of class, age, gender, sexuality, and race into the scholarship. Essays span the United States and Canadian border, exploring gender violence, sexual harassment, the violent kidnapping of union organizers, the violence of inadequate health and safety protections, the culture of violence in state institutions, the mythology of working-class violence, and the changing nature of violence in extractive industries. The Violence of Work theorizes and historicizes violence as an integral part of working life, making it possible to understand the full scope and causes of workplace violence over time. –Publisher's description, Contents: Introduction: Accounting for violence / Jeremy Milloy – The perils of sex work in Montreal: seeking security and justice in the face of violence, 1810-1842 / Mary Anne Poutanen – The rules of discipline: workers and the culture of violence in progressive-era reform schools / James Schmidt – The "new solution": anti-labour kidnapping, D.B. McKay, and the legacy of the second Seminole War / Chad Pearson – Billy Gohl: labour, violence, and myth in the early twentieth-century Pacific Northwest / Aaron Goings – Slow violence and hidden injuries: the work of strip mining in the American west / Ryan Driskell Tate – The murder of Lori Dupont : violence, harassment, and occupational health and safety in Ontarion / Sarah Jessup – "By the nuimbers" : workers' compensation and the (further) conventionalization of workplace violence / Robert Storey – Gender violence in the hospitality industry: panic buttons, pants, and protest / Emily E. LB. Twarog.
OCLC: 1252731475